A PENGARUH MEDIA PEMBELAJARAN QUIZIZ GAME TERHADAP HASIL BELAJAR PRAKTIKUM AKUNTANSI PADA SISWA KELAS XI AKL SMKN 1 POLEWALI MANDAR: QUIZIZZ GAME, HASIL BELAJAR, PRAKTIKUM AKUNTANSI, SMKN 1 POLEWALI MANDAR - azhizha, hasnur; Tikollah, M. Ridwan; Sahade (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
ABSTRACT This study aims to determine the effect of quiziz game learning media on accounting learning outcomes in class XI Accounting SMK 1 Polewali Mandar. The variables in this study are quiziz games as the independent variable (X) and learning outcomes as the dependent variable (Y). The population of this study were all students of class XI Accounting at SMKN 1 Polewali Mandar. The sampling technique used purposive sampling, the classes taken were XI Accounting 1 totaling 30 students and XI Accounting 2 totaling 35 students. Data collection techniques using documentation, observation, tests and questionnaires. The data analysis technique used is instrument test consisting of validity and reliability tests, requirements analysis test namely normality test and hypothesis testing consisting of Mann-Whitney and N-gain tests. The research results showed that: (1) The pretest learning outcomes of all students in the control class and experimental class, namely 30 students each, were still below the KKM score. (2) The posttest learning outcomes in the control class which achieved the KKM score were 9 students with a maximum score of 100 and a minimum score of 75, and those who did not achieve the KKM score were 21 students with a maximum score of 70 and a minimum score of 40. As for the experimental class which achieved a KKM score as many as 30 students with a maximum score of 100 and a minimum of 75, and no student who did not reach the KKM score. (3) Based on the results of the Mann-Whitney test on the posttest learning outcomes of the control class and the experimental class, an Asymp.sig (2-tailed) value of 0.001 > 0.05 was obtained. This shows that the use of Quiziz Game media can significantly influence student learning outcomes so that the hypothesis is accepted. (4) Based on the results of the N-Gain test, the average score obtained by the control class was 34.11 and the average value for the experimental class was 77.18. So it can be concluded that the use of Quiziz Game learning media is effective for improving learning outcomes while conventional learning media/package books are not effective for improving learning outcomes.